2008
DOI: 10.1007/s00024-008-0315-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Wing Crack Extension: Implications for the Ingredients of Discrete Element Model

Abstract: In this study, we investigate what basic mechanisms a Discrete Element Model should have in order to reproduce the realistic wing crack extension, a widely observed phenomenon in uni-axial compression of brittle material with pre-existed crack. Using our Discrete Element Model-the Lattice Solid Model, we study how cracks propagate when different force-displacement laws are emplyed. Our results suggest that the basic features of crack propagation observed in laboratories cannot be reproduced under the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Experimentally, it is difficult to generate closed flaws with controlled properties [9], but some results suggest similar crack propagation patterns from open or closed flaws [9,6,4]. Closed flaws were simulated in DEM in 2D [32] and in 3D [33], with, however, contradictory conclusions regarding the numerical requirements for wing crack simulations. This will be discussed in section 5.2, considering different approaches to model closed flaws.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it is difficult to generate closed flaws with controlled properties [9], but some results suggest similar crack propagation patterns from open or closed flaws [9,6,4]. Closed flaws were simulated in DEM in 2D [32] and in 3D [33], with, however, contradictory conclusions regarding the numerical requirements for wing crack simulations. This will be discussed in section 5.2, considering different approaches to model closed flaws.…”
Section: Introductionmentioning
confidence: 99%
“…We notice that the choice here of linear elastic springs was motivated by computational simplicity and evidence from previous studies that this type of elastic bond already allows for capturing the most relevant mechanical features of both regular and irregular lattices of bonded particles, including fracture phenomenology [33][34][35][36]. In Equation (1), K r ¼ 2.9775 Á 10 7 is the radial compressional/tensional spring stiffness.…”
mentioning
confidence: 99%
“…In DLSM, only tensile and shear springs are incorporated. However, Wang and Mora conducted the simulation on the same geometry (refer to Figure C) and concluded that the correct path cannot be reproduced without considering particle rotation in their Lattice Solid Model, which resulted in the situation that the cracks “grow slowly and discontinuously, and several en echelon cracks appear” . The correct path can only be reproduced when normal, shear stiffness, bending stiffness, and single particle rotation are all included in their models.…”
Section: Two‐dimensional Distinct Lattice Spring Modelmentioning
confidence: 99%
“…(B) DLSM simulation. (C) LSM simulation without particle rotation from Wang and Mora [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Two‐dimensional Distinct Lattice Spring Modelmentioning
confidence: 99%